Implementasi Model SECI dalam Perencanaan Pulang untuk Kesiapan Pasien Stroke dalam Pemulangan: Literatur Riview - Sy, Yunizabetri; Huda, Nurul; Bayhakki (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Discharge planning is a crucial element in nursing care, especially for patients recovering from severe medical conditions like ischemic stroke. Effective discharge planning influences patient outcomes, including recovery levels and quality of life. This literature review aims to explore studies on the implementation of the SECI model in discharge planning for ischemic stroke patients. Databases used include Google Scholar, PubMed, ScienceDirect, Semantic Scholar, ResearchGate, and BMC, with a systematic literature review method. Keywords used were "ischemic stroke" and "discharge planning." A total of 120 articles were retrieved from the literature search, which were then filtered using the PICO framework and CRAAP criteria. The SECI model-based discharge planning was found to be more effective than standard methods. To enhance discharge planning for ischemic stroke patients, hospitals and nurses need to train nurses in the SECI model and develop audiovisual-based educational modules. Good communication among healthcare team members should be maintained, and families need to be involved in the discharge process. Regular evaluations are also essential to identify improvements and gather feedback from patients and families